2009
DOI: 10.1002/bit.22346
|View full text |Cite
|
Sign up to set email alerts
|

Energy from algae using microbial fuel cells

Abstract: Bioelectricity production from a phytoplankton, Chlorella vulgaris, and a macrophyte, Ulva lactuca was examined in single chamber microbial fuel cells (MFCs). MFCs were fed with the two algae (as powders), obtaining differences in energy recovery, degradation efficiency, and power densities. C. vulgaris produced more energy generation per substrate mass (2.5 kWh/kg), but U. lactuca was degraded more completely over a batch cycle (73 +/- 1% COD). Maximum power densities obtained using either single cycle or mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(113 citation statements)
references
References 34 publications
(37 reference statements)
4
107
1
1
Order By: Relevance
“…Many types of algal biofuel have been considered, including biogas, bio-hydrogen, algal fuel cells, bioethanol and direct algal biomass combustion (Benemann, 2000;Kruse & Hankamer, 2010;McKendry, 2002;Strik, Terlouw, Hamelers, &Buisman, 2008;Velasquez-Orta, Curtis, & Logan, 2009;Verma, Mehrotra, Shukla, & Mishra, 2010).The demand for liquid fuels, however, coupled with the potential high lipid content of some microalgal species under certain conditions, has resulted in much of the work focusing on the production of biodiesel and other liquid biofuels derived from microalgal lipids.. Unfortunately after some 70 years of research Many types of filters have been used to harvest algae and filtration has been found satisfactory at recovering relatively large algal cells (Molina Grima, Belarbi, Acien-Fernandez, Robles-Medina, & Yusuf, 2003), but can be hampered by low through put and rapid clogging (Mohn, 1988;Oswald, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Many types of algal biofuel have been considered, including biogas, bio-hydrogen, algal fuel cells, bioethanol and direct algal biomass combustion (Benemann, 2000;Kruse & Hankamer, 2010;McKendry, 2002;Strik, Terlouw, Hamelers, &Buisman, 2008;Velasquez-Orta, Curtis, & Logan, 2009;Verma, Mehrotra, Shukla, & Mishra, 2010).The demand for liquid fuels, however, coupled with the potential high lipid content of some microalgal species under certain conditions, has resulted in much of the work focusing on the production of biodiesel and other liquid biofuels derived from microalgal lipids.. Unfortunately after some 70 years of research Many types of filters have been used to harvest algae and filtration has been found satisfactory at recovering relatively large algal cells (Molina Grima, Belarbi, Acien-Fernandez, Robles-Medina, & Yusuf, 2003), but can be hampered by low through put and rapid clogging (Mohn, 1988;Oswald, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of proteins, carbohydrates and lipids, serves as nutrient source for the microbes. Hence use of algae biomass in MFC is a promising approach to generate electricity (Strik et al 2008;Velasquez-Orta, Curtis and Logan, 2009;Yuan et al 2011;Lakaniemi, Tuovinen and Puhakka, 2012;Rashid et al 2013;Kondaveeti et al 2014;Gajda et al 2015). Experimental data illustrated the feasibility and sustainability of using cynobacterial biomass as anodic substrate with microbial strain of B. firmus NMBL-03 in MFCal for bioelectricity generation.…”
Section: Electricity Production Using Hydrolysate Algae Substratementioning
confidence: 98%
“…These electrons are captured by a suitable anode, which then combine with protons and oxygen in the cathode chamber to form water and usable electric current [16]. Most common microbes being used in MFCs are bacteria [16], yeast [17] and algae [18,19]. Microbial fuel cells are capable of harvesting more than 90 % of the electrons from organic compounds.…”
Section: Introductionmentioning
confidence: 99%